If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + x + 23 + 23 = 0 Reorder the terms: 23 + 23 + x + x = 0 Combine like terms: 23 + 23 = 46 46 + x + x = 0 Combine like terms: x + x = 2x 46 + 2x = 0 Solving 46 + 2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-46' to each side of the equation. 46 + -46 + 2x = 0 + -46 Combine like terms: 46 + -46 = 0 0 + 2x = 0 + -46 2x = 0 + -46 Combine like terms: 0 + -46 = -46 2x = -46 Divide each side by '2'. x = -23 Simplifying x = -23
| 8a+5b=44 | | 4x+24=23 | | -5x+3(-6x+8)=-252 | | 10msquared= | | 3(2-3x)=2(-4x+7) | | exp(-0.1X^2)= | | 9/10-4/10= | | 2/5(x-9/40=3/10(7-2x) | | 2p+x+4p= | | 6x-(7+4x)= | | a^2(b-4)-25(b-4)=0 | | z=3x+9y | | -6y+x=5 | | 5/7x8/15 | | Y-6=-4(x+7) | | N^2-14n+69=-8 | | Ln(5x-8)=1 | | x=6x+5 | | 4x+37=100 | | 2v^2=15+7v | | 8x^3-9ax^2+a^3=0 | | 2x^-5u^7/14x^6y^3 | | 9x-5x+10=2x^2-4x | | 0=12x^3-12x | | 0=12x^3+12x | | 0=12x^3+12x^2 | | 5v^2=-6+13v | | x+2*y=100 | | 6x^2-35-49=0 | | F(x)=4x^3-7x^2+3x-10 | | (6r+4s)(6r+4s)= | | 10r^2-19r=56 |